2016
DOI: 10.1002/glia.23058
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the astrocytic Nrf2/ARE system ameliorates the formation of demyelinating lesions in a multiple sclerosis animal model

Abstract: Oxidative stress critically contributes to the pathogenesis of a variety of neurodegenerative diseases such as multiple sclerosis. Astrocytes are the main regulators of oxidative homeostasis in the brain and dysregulation of these cells likely contributes to the accumulation of oxidative damage. The nuclear factor erythroid 2-related factor 2 (Nrf2) is the main transcriptional regulator of the anti-oxidant stress defense. In this study, we elucidate the effects of astrocytic Nrf2-activation on brain-intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 55 publications
(81 reference statements)
2
71
0
Order By: Relevance
“…7), in line with a recent study that demonstrated that ablation of Erk2 in the CNS reduced the levels of immune mediators, gliosis and demyelination in the cuprizone model (Okazaki et al 2016). Consistent with the critical role of astrocytes in toxin induced demyelination, forced over-activation of astrocytic Nrf2, a main transcriptional regulator for the anti-oxidative defense system, through GFAP-specific deletion of the Nrf2 repressor Keap1 , ameliorates the cuprizone-induced loss of oligodendrocytes and inflammation (Draheim et al 2016). While the loss of S1pr1 in astrocytes diminished the therapeutic efficacy of FTY720 during EAE (Choi et al 2011) and FTY720 suppresses pathogenic astrocyte activation and chronic disease progression (Rothhammer et al 2017), further investigation of cell-type specific targeting of S1pr1 is required to definitively delineate the exact role of S1PR1 signaling in the context of demyelination and neurodegeneration.…”
Section: Discussionmentioning
confidence: 84%
“…7), in line with a recent study that demonstrated that ablation of Erk2 in the CNS reduced the levels of immune mediators, gliosis and demyelination in the cuprizone model (Okazaki et al 2016). Consistent with the critical role of astrocytes in toxin induced demyelination, forced over-activation of astrocytic Nrf2, a main transcriptional regulator for the anti-oxidative defense system, through GFAP-specific deletion of the Nrf2 repressor Keap1 , ameliorates the cuprizone-induced loss of oligodendrocytes and inflammation (Draheim et al 2016). While the loss of S1pr1 in astrocytes diminished the therapeutic efficacy of FTY720 during EAE (Choi et al 2011) and FTY720 suppresses pathogenic astrocyte activation and chronic disease progression (Rothhammer et al 2017), further investigation of cell-type specific targeting of S1pr1 is required to definitively delineate the exact role of S1PR1 signaling in the context of demyelination and neurodegeneration.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, a new study has shown that astrocytes with mutant SOD1 increase P-glycoprotein in endothelial cells in vitro [44]. Moreover, astrocytic Nrf2 activation helps to prevent oligodendrocyte loss and demyelination in an animal model of multiple sclerosis [45]. These data suggest that induction of Nrf2 in astrocytes contributes to neuroprotection, BBB repair, and white matter recovery after various brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Maybe most importantly, in contrast to EAE T-cells are not relevant for cuprizone-induced demyelination. This leads to oxidative stress (36) and in consequence to primary oligodendrocyte apoptosis which is closely followed by microglia and astrocyte activation (see Figure 4A). Furthermore, breakdown of the blood-brain barrier, a hallmark of MS and EAE, is not a characteristic feature of the cuprizone model (5).…”
Section: The Cuprizone Modelmentioning
confidence: 99%